What drives entrepreneurial intention? - Wanda Novita (Priviet Social Sciences Journal, 2025)
Entrepreneurial intention is a critical determinant of business venture sustainability, particularly among small and medium-sized enterprise (SME) owners. This study investigates the influence of social media, motivation, and creativity on entrepreneurial intention using the framework of Social Learning Theory. A quantitative research design was employed, with data collected through an online survey administered to 61 SME owners in South Tangerang, all of whom have operated their businesses for a minimum of three years and employed at least five staff members. The data were analyzed using multiple linear regression analysis via SPSS version 26. The findings demonstrate that social media exerts a positive and statistically significant effect on entrepreneurial intention, whereas motivation and creativity have no significant impact. From a theoretical perspective, this study contributes to the application of Social Learning Theory in the context of established entrepreneurship. Practically, the results underscore the strategic importance of social media as a tool for fostering entrepreneurial learning and community engagement, thereby enhancing the entrepreneurial intentions of experienced SME owners.